Open Unemployment in South Kalimantan: Can School Participation and Workforce Rates Affect It? - Zulhikmah, Nurlina; Dahliana, Difi; Nilasari, Erissa (JURNAL EKONOMI DAN BISNIS (EKOBIS-DA), 2025)
Unemployment is created as a result of the increase in job vacancies being lower than the increase in the workforce, resulting in a large number of unemployed workers in the economy. This study aims to analyze the regression of school participation rates, workforce, and open unemployment in South Kalimantan. The research method used is quantitative with secondary data for the period 2017-2022. The data is processed using Eviews 12 to conduct classical assumption tests and multiple regression tests. The research findings show that the school participation rate and workforce do not have a significant effect on open unemployment in South Kalimantan Province from the period 2017-2022, either partially or simultaneously. This finding contributes to deepening insight into the factors that influence unemployment cannot always be linked to school participation rates and the workforce.